Efeitos do exercício físico de salto sobre as proteínas relacionadas à captação de glicose e via proteolítica dependente de ATP no músculo gastrocnêmio de ratos diabéticos induzidos por administração de aloxana - Batista, Rogério de Oliveira [UNESP] (2014)
The literature suggests that in diabetes mellitus, the gene expression of proteins involved in UPS (ubiquitine - proteasome system) lies above baseline levels, causing degradation of myofibrillar proteins. It is known that E214kDa conjugating enzyme and ubiquitin ligase E3 - MuRF1 (Muscle Ring Finger -1) may be regarded as biomarkers of this pathway. The models of diabetic animals shows increased expression of NFkB (Nuclear Factor kappa B), which plays an important role in the regulation of GLUT4 gene transcription. Exercise appears as a therapeutic method in the treatment of diabetes mellitus. Muscle contraction improves glucose uptake in skeletal muscle GLUT4 translocating protein kinase pathway activated by 5' - AMP (AMPK). Objective: To evaluate the effect of six weeks of jumping on GLUT4 protein content of training, and gene expression (mRNA) of Slc2a4 (GLUT4 protein), UBB (Ubiquitin), E214kDa, Trim63 (MuRF1 protein) , NFkB p105 gene and Prkaa2 (AMPKα2) protein in the gastrocnemius muscle of diabetic rats...